Pelestarian Budaya Jawa Oleh Sekolah Budaya Tunggulwulung di Kota Malang, Jawa Timur - Moh. Pebrianto; Nur Hadi (Mahesa Research Center, 2021)
This study aims to describe the process of the formation of the Tunggulwulung School of Culture (SBT) in Malang and the form of Javanese cultural preservation carried out by the school of culture. This study uses a qualitative research approach. The process of extracting data was carried out by observation, interviews, and documentation, and literature study. The results showed that the Tunggulwulung School of Culture (SBT) was established to preserve the culture and artistic heritage of the ancestors, particularly Javanese culture and arts. The activities carried out at the Tunggulwulung School of Culture (SBT) include ngangsu kaweruh or conducting studies on cultural history and heritage arts (especially Javanese culture), and others. Based on the AGIL concept by Parsons, the Tunggulwulung School of Culture (SBT) can survive and develop until today due to four aspects. The first is an adaptation, the Tunggulwulung School of Culture (SBT) adapts by freeing people to participate in activities according to their interests and wishes, and free of charge. The second is goal achievement. The school has various activities that are used as a basis for achieving the goal, namely preserving Javanese culture. Then the integration is carried out through the formation of an organizational structure, as well as holding various activities and promotions. The last one is latency, the Tunggulwulung School of Culture (SBT) maintains patterns or systems through innovation in learning models, activities, and promotions.